Communal therapeutic mobility in group walking: A meta-ethnography. (October 2020) - Pollard, Tessa M.; Guell, Cornelia; Morris, Stephanie
Abstract: Increased attention to links between walking, health and wellbeing have contributed to a growth in the number of walking groups meeting on a regular basis to offer short, social walks. Walking group interventions are known to increase physical activity and to have wide-ranging health benefits, and there is evidence that drop out is generally low. The aim of this paper is to synthesise qualitative research on experiences and perceptions of group walking in order to develop a new conceptual understanding of the group walking experience. We conducted a systematic search of the literature and identified 22 such studies which we synthesised using meta-ethnography. Included studies were conducted in the UK, USA, Australia and Ireland. Most reported research was undertaken with outdoor walking groups, some of which catered specifically for people who shared a disease experience or a disability. A smaller number of studies examined indoor mall walking groups, while two looked at perceptions of non-participants of group walking as a potential activity. From the original constructs identified in the papers we derived five higher order constructs: seeking and enjoying health and fitness, attachment to walking, providing purpose and confidence, mobile companionship and a peaceful and contemplative shared respite from everyday life. We argue that participating in a walking group provides a set of experiences that together constitute a specific form of shared or communal therapeutic mobility that is not simply the accumulation of the constructs we have outlined. Rather, we suggest that an initial instrumental and disciplinary focus on health and fitness is transformed through the experience of group walking into a shared meaningful and enjoyable practice; an emergent communal therapeutic mobility, which recruits and retains large numbers of group walkers. However, this communal therapeutic mobility is not equally accessible to all. Highlights: Develops a new understanding of the group walking experience using meta-ethnography Identifies an initial disciplinary focus on health and fitness in group walking Argues this is transformed into a shared meaningful and enjoyable practice Introduces the concept of communal therapeutic mobility/ies Locates inequalities in access to communal therapeutic mobility in group walking